2012
DOI: 10.1002/ana.22654
|View full text |Cite
|
Sign up to set email alerts
|

Connexin hemichannel blockade improves outcomes in a model of fetal ischemia

Abstract: These data support the hypothesis that opening of connexin hemichannels is a significant mediator of postischemic white and gray matter dysfunction and injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
145
6
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(168 citation statements)
references
References 48 publications
(57 reference statements)
15
145
6
1
Order By: Relevance
“…ADP, adenosine diphosphate; Cyt C, cytochrome C. injury, in vitro, P2X7 receptor antagonists, enzymatic ATP degradation, and hemichannel blockade all reduced oligodendrocyte mitochondrial depolarization and oxidative stress, reduced ischemic damage to optic nerves (77), and improved functional recovery after ischemia (77). These data are highly consistent with the finding of reduced seizure activity after hemichannel blockade (71).…”
Section: Mechanisms Of Perinatal Brain Injurysupporting
confidence: 72%
See 2 more Smart Citations
“…ADP, adenosine diphosphate; Cyt C, cytochrome C. injury, in vitro, P2X7 receptor antagonists, enzymatic ATP degradation, and hemichannel blockade all reduced oligodendrocyte mitochondrial depolarization and oxidative stress, reduced ischemic damage to optic nerves (77), and improved functional recovery after ischemia (77). These data are highly consistent with the finding of reduced seizure activity after hemichannel blockade (71).…”
Section: Mechanisms Of Perinatal Brain Injurysupporting
confidence: 72%
“…This included a dramatic reduction in seizures and the incidence of status epilepticus, improved recovery of EEG power, and sleep state cycling, and improved survival of oligodendrocytes, with intermediate neuronal survival between sham controls and vehicle-treated animals. The improved recovery of EEG activity with postischemic hemichannel blockade may be related to better cortical cell survival as suggested by the strong correlation between EEG power and cortical neuronal number (71). Improved cell survival was likely related to a combination of acutely reduced injury spread and subsequently reduced astrogliosis and chronic inflammation, as shown recently after spinal injury in adult rats (72).…”
Section: Mechanisms Of Perinatal Brain Injurymentioning
confidence: 67%
See 1 more Smart Citation
“…A mimetic peptide that blocks Cx43 hemichannels after perfusion into the lateral ventricle reduces seizure activity and improves the survival of oligodendrocytes and neurons after ischemia in sheep [42] .…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that hypothermia promoted the diferentiation and maturation of oligodendrocyte precursor cells (OPCs), and indicated that OPC death was signiicantly suppressed by hypothermia in vitro, alluding to the fact that hypothermia is protective of oligodendrogliogenesis [126]. More recent studies in fetal sheep have shown that cerebral ischemia is associated with signiicant loss in total numbers of oligodendrocytes, decreased myelin basic protein expression, and increased microglial activation [127,128]. However, another study in fetal sheep countered these results by showing that delayed cerebral hypothermia partially protects white mater after global cerebral ischemia by stimulating oligodendrocyte proliferation, reducing microglial induction, and restoring the amount and patern of expression of myelin basic protein, once again conirming the neuroprotective role of hypothermia toward oligodendrogenesis [129,130].…”
Section: Gliogenesismentioning
confidence: 99%